Unexpected Formation of Bis(hydrazinecarboximidamide) via Ultrasound Promoted Rearrangement of Epoxy Ketone - Silvania Rizzi Brasil; Adriana do Carmo Capiotto; Alex Fabiani Claro Flores; Davi Fernando Back; Eliandro Faoro; Lucas Pizzuti (Orbital: The Electronic Journal of Chemistry, 2017)
An efficient synthesis of aromatic pyrazoles via cyclocondensation of epoxy chalcones with hydrazine is reported. When aminoguanidine hydrochloride is the dinucleophilic specie the reaction leads to a mixture of amidino pyrazole and a minor amount (15%) of an interesting co-product identified as 2,2'-(1,3-diphenylpropane-1,2-diylidene)bis(hydrazinecarboximidamide) dihydrochloride by X-ray diffraction and NMR. A plausible mechanism for the co-product formation via rearrangement of the epoxy chalcone into 1,2-diketone followed by the condensation with aminoguanidine reaction is proposed.DOI: http://dx.doi.org/10.17807/orbital.v9i3.972